Switching transient analysis for low voltage distribution cable - Mishra Sanhita; Swain Sarat Chandra; Dash Ritesh (Open Engineering, 2022)
Low voltage cable is primarily connected from the transmission system to several household applications. It is quite common that switching transient in the power system during the energization of the high voltage and low voltage cables have a very crippling effect on the cable as well as the power system components. Hence, an experiment has been performed in the laboratory with a low voltage cable-connected motor system. The experimental results have been validated in the simulation platform, and they are capable of predicting the transient behavior during power cable energization. The effect of transients on power cables during the energization of devices has been investigated in this study in the form of voltage, current, and frequency. Discrete wavelet transform is implemented for the decomposition of the transient current. The generated approximation signal is used to quantify the severity during switching transient condition.